Visual Representation in Reading Text for Students of Elementary School - Dionysius Nazario Setiaji; Agnes Widyaningrum (Universitas PGRI Semarang, 2023)
The importance of learning English skills, namely reading aimed at improving English mastery, is very important for students. Though there are some students who have difficulty in learning English subject in class. Therefore, I conducted research using classroom action research about the use of visual images to find out whether pictures can improve students' reading comprehension mastery or not. This research was conducted in 6 steps, namely identifying, planning, collecting data, analysing and interpreting data, reflecting and sharing, and taking action. This subject of the study are fourth graders of SDN Ngaliyan 05 Semarang. The results showed that their average pre-test score was 41 and the average post-test score was 74. The finding shows that using visual images can help them to learn reading comprehension.